The Dynamics of Resilience Formation In Broken Home Youth - Boru, Lanny Octa Merliana; Anakaka, Dian Lestari; Pello, Shella Christine (Universitas Nusa Cendana, 2023)
Broken home is a family condition that is no longer intact because of the separation or divorce of the parents. The condition of a broken home creates psychological pressure for adolescents, so that adolescents need the ability to survive and adapt in order to rise from the pressure they receive, this ability is called resilience. This study aims to see a picture of resilience in broken home adolescents. The method used in this research is a qualitative approach. The data collection technique used in this study is the photovoice technique using semi-structured interviews, data analysis techniques using thematic analysis. The participants involved in this study were 4 teenagers who had legally divorced parents and who were in the city of Kupang who were selected based on the snowball sampling technique. The results of the study show that resilience in broken home adolescents is related to four main themes namely the impact of a broken home, active coping, support system and resilience characteristics.